RANCANG BANGUN ALAT PENCACAH RUMPUT SEDERHANA BERBASIS MOTOR LISTRIK - I Made Ivan Wiyarta Cakra Sujana; Martina Puspita Sari; Azhar Syafiq Putra; Ahmad Maulana Adi Nugroho; Alya Azzahra Salsabila; Zainal Jayadi; Brithanio Kila Seno Padang; Bima Wahyu Ramadhan (Politeknik Negeri Sriwijaya, Indonesia, 2026)
Forage grass is the main feed for ruminant livestock such as cattle and goats. However, the chopping process is still mostly done manually using a sickle, which is inefficient and requires considerable time and energy. This research aims to design and fabricate a simple grass chopper machine powered by an electric motor that is economical, compact, and easy to operate by small-scale farmers. The methods used include component design using 3D software, mechanical calculations (transmission, force, power, torque, shaft diameter), fabrication of the tool, and load simulation analysis using simulation software. The results showed that the machine uses an electric motor with a blade rotational speed of 835.71 rpm, driving force of 9.81 N, and power of 60.07 W. The motor side shaft diameter is 8 mm, while the blade side shaft is 10 mm. Simulation results indicated a maximum stress of 13,670 N/m², which is far below the yield strength of ironwood (ulin wood) at 55.64 MPa, resulting in a safety factor of 4068.9, indicating that the structure is safe. The maximum displacement is 0.00321 mm and maximum strain is 2.99 x 10⁻⁶, showing very small deformation, thus the structure is stiff and stable. The total fabrication cost of the tool is IDR 634,000. This grass chopper machine is deemed feasible for use and can improve the work efficiency of small-scale farmers.